Differences in Psychological Well-Being Between Healthcare Professionals and Health Science Students Participating in a Psychological Well-Being Training Program - Nova Khairunnisa; Fasayu Berliana Agustin; Fuad Minan Zuhri; Rizqi Ulin Nuha; Imam Faisal Hamzah (Knowledge Dynamics, 2026)
Background: Psychological well-being (PWB) refers to an individual’s ability to accept oneself, establish positive relationships with others, demonstrate autonomy in decision-making, manage environmental demands, maintain a clear sense of purpose in life, and continuously experience personal growth. In the healthcare context, PWB is essential because it is closely related to the quality of healthcare services and the effectiveness of the educational process among health science students. Differences in professional experience and developmental stages between healthcare professionals and students may lead to variations in their PWB profiles. This study aimed to analyze differences in PWB healthcare professionals and health science students who participated in a PWB training program. Methods: This study employed a quantitative approach using a cross-sectional comparative design. The participants consisted of 194 individuals, including 105 active healthcare professionals and 89 health science students who participated in a PWB training program organized by the Health Division of the Regional Board of the Muhammadiyah Student Association in Central Java. PWB was assessed using a questionnaire adapted from the instrument developed by Kartika (2014) and grounded in Ryff’s PWB model, which encompasses six core dimensions for evaluating PWB among healthcare professionals and health science students. Data were analyzed using the Mann–Whitney U test to examine differences between the two groups. Results: The results showed that most indicators of PWB differed significantly between healthcare professionals and health science students, particularly in the dimensions of self-acceptance, autonomy, and environmental mastery. Conclusion: There are significant differences in PWB profiles between healthcare professionals and health science students. These findings highlight the importance of developing PWB training programs that consider the specific needs and characteristics of each group so that mental health interventions can more effectively support healthcare service quality and educational processes in the health sector.